The Emotional Intelligence, Occupational Stress, and Coping Characteristics by Years of Nursing Experiences of Newly Hired Oncology Nurses - Ann M Mazzella-Ebstein; Kay See Tan; Katherine S Panageas; Judith E Arnetz; Margaret Barton-Burke (Elsevier, 2021)
Objective: The objective of the study was to compare and analyze the emotional intelligence, occupational stress, and coping characteristics of three groups of newly hired oncology nurses. Methods: Data for this secondary analysis were collected from a larger study of 114 newly hired nurses at a cancer center in the Northeastern United States. Survey data were collected using the EQi-2.0™, the Nursing Stress Scale, and the Ways of Coping Questionnaire. Dimensions of study measures were analyzed based on new graduates, 1-5 years, and >5 years of nursing experience. Analysis of variance was conducted among the three groups followed by Tukey pairwise comparisons analysis when P = 0.05. Results: New graduates scored significantly lower on the self-expression dimension (mean = 96.88; standard deviation [SD] = 13.27) than nurses with >5 years nursing experience (mean = 106.12; SD 15.02) (P = 0.04), and the subdimension, assertiveness (mean = 94.73; SD = 13.87) compared to nurses with >5-year nursing experience (mean = 103.94; SD = 14.86) (P = 0.03). Significantly higher sources of stress for new graduates were death and dying (mean = 16.45; SD = 3.37), and for the associations between the three nursing groups (P = 0.001). New graduate nurses used the problem-focused coping strategy of accepting responsibility (mean = 14.06; SD = 7.28) significantly (P = 0.006) more often than nurses with >5-year experience (mean = 8.54; SD = 4.25), and planful problem solving (mean = 16.76; SD = 5.27) significantly less often (P =.001) than nurses with 1-5-year experiences (mean = 20.12; SD = 7.31). Conclusions: Dimension scores highlight the characteristics of nurses with varying levels of nursing experience onboarding at the same time. Findings may inform model-development for improving nurse-recruitment practices and retention strategies.